MENGELOLA FAKTOR PRODUKSI SECARA EFISIEN - Siti Salbiyah (UMSurabaya Publishing, 2011)
Every company wants to achieve the purpose of achieving profit / maximum profit. Maximum advantage can be obtained if a company successfully organizing factors of production efficiently. Efficient question is if the company succeeded in creating certain goods financed with only minimal sacrifice. Or particular business / certain sacrifices can yield the optimal output.Â The purpose of this paper is to provide an overview of employers or the reader about how to manage the factor-factor production efficiency in order to obtain the cost of a cheap product. An entrepreneur who can organize the factors of production efficiently, then he will succeed in achieving economies of scale that is creating the maximum product of a certain sacrifice. If the maximum product items can be created from the cost / certain sacrifice, then of course the price of goods per unit of product it will be low. If the cost of the product is low, then the entrepreneur will win the competition in the market, because every consumer will always try to get the desired price is cheap. If he can manage the factors of production efficiently and cost of production goods will become cheaper, and certainly will be preferred by consumers, and leads to increased sales volume. This means that maximum benefit can be achieved according to the desired destination from the beginning.Key words: efficiency, factors of production, the cost of productionÂ